2006
DOI: 10.1590/s1020-49892006000400003
|View full text |Cite
|
Sign up to set email alerts
|

Gravidez na adolescência e exclusão social: análise de disparidades intra-urbanas

Abstract: The results showed that adolescent girls with little schooling and a lower socioeconomic level were more likely to give birth. Specific actions should be promoted to prevent pregnancy in this group and to foster the social inclusion of these adolescents and their children, providing them with opportunities to improve their socioeconomic situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
21

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 10 publications
1
10
0
21
Order By: Relevance
“…A frequência de gravidez na adolescência tem grande variação e depende da situação social e econômica da região, sendo mais incidente nas regiões menos desenvolvidas e menos urbanizadas 12,23 23 . Estudo de Campinas mostrou que 48,4% das adolescentes tinham escolaridade de até sete anos de estudo em relação a 43,3% das adultas 9 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A frequência de gravidez na adolescência tem grande variação e depende da situação social e econômica da região, sendo mais incidente nas regiões menos desenvolvidas e menos urbanizadas 12,23 23 . Estudo de Campinas mostrou que 48,4% das adolescentes tinham escolaridade de até sete anos de estudo em relação a 43,3% das adultas 9 .…”
Section: Discussionunclassified
“…O parto pré-termo é intercorrência obstétrica com maior frequência entre adolescentes em comparação com gestantes de outras faixas etárias 11,12 . O aumento dos índices de gravidez na adolescência pode contribuir para maior prevalência de parto pré-termo, apesar da etiologia dos aspectos obstétricos da prematuridade ser multifatorial.…”
Section: Introductionunclassified
“…Among the main already established factors, we can highlight variables related to demographics, education, sexual and contraceptive behavior, and psychosocial factors concerning the teenager and her family. The literature shows associated factors such as: adverse socioeconomic situation, 5,6 becoming sexually active early in life, 8,10,16 higher frequency of sexual intercourse, 11,20,21 lack of use or inconsistent use of contraceptive methods, 11,20 lower expectations on the part of the teenager concerning schooling and professional performance in the future, 9,10 among others. In regard to family functioning and structure, studies have shown significant associations between teenage pregnancy and low schooling of the father and/or mother, early pregnancy of the teenager's biological mother, dysfunctional family relationships, such as early death of the mother, and absence of a father fi gure.…”
Section: Introductionmentioning
confidence: 99%
“…Entre escolares do Município de São Paulo, ter maior escolaridade mostrou-se significativamente associado ao conhecimento sobre mé-todos contraceptivos, sendo a RP entre aqueles com maior escolaridade de 1,51 (IC95%: 1,17-1,95) comparados aos que apresentaram menor tempo de estudo 4 . Dois outros estudos indicam também que o grau de escolaridade é fator de proteção para questões relacionadas à sexualidade e prática sexual 7,15 . Em um deles, o risco de engravidar foi 58% menor para adolescentes com cinco anos ou mais de escolaridade em relação aos demais 7 .…”
Section: Discussionunclassified